Efektivitas Penatalaksanaan Tindakan Invasif Minimal Pada Hemoroid : Rubber Band Ligation - Anasthasia F. M. Ayomi; Fitriyani; Anggraini Janar WUulan; Putu Yunita (Medula, 2019)
Hemorrhoids are dilation of blood vessels from the hemorrhoid plexus. In the United States around 10 million suffer from hemorrhoids. The exact diagnosis of hemorrhoids can be obtained from histopathological examination. Although hemorrhoids are not dangerous, however, if widening of the vein becomes wider, we still need to prevent it. Prevention by increasing eating high-fiber foods, such as fruits and fresh vegetables. One of the minimally invasive actions that can be done is like a rubber band ligation. This action is quite good, easy, and inexpensive because it can be done in a practical place with simple tools and without involving complicated procedures such as the hemorrhoidectomy process. Some studies mention the action of rubber band ligation effectively used in internal hemorrhoids in degrees II and III although there are still minimal complications such as bleeding and a sense of discomfort.